Identification of Physics Misconceptions Using Five-tier Diagnostic Test: Newton’s Law of Gravitation Context - Zikra Juita; Putri Dwi Sundari; Silvi Yulia Sari; Fanny Rahmatina Rahim (Postgraduate, University of Mataram, 2023)
Students' understanding of several topics in physics is still low. The teachers only focus on completing curriculum targets without considering their student's understanding and most of them have misconceptions. The study aimed to identify students' misconceptions of physics concepts using the five-tier diagnostic test. Data was collected once using a descriptive-quantitative method. The research sample consisted of 18 students from one of the high schools in West Sumatra. A total of 17 questions was used to identify students' understanding of Newton's law of gravitation. The results showed that students had misconceptions as follows: gravitational attraction is only caused by planets; there is no gravitational force in space, and the direction of the gravitational force is determined by the direction of the gravitational attraction by some objects; two objects have different gravitational force strengths; all planets revolve around one another, the orbit of the solar system is perfectly circular, the shape of the earth is round, and the strength of the gravitational field is affected by the mass of the object. In conclusion, the highest percentage of misconceptions occurs in the influence of the gravitational field strength, which was 23%.